ISOTOPIC RATIOS AS A TOOL FOR STUDYING SOURCES OF COPPER, LEAD, AND ZINC IN NATURAL AND URBAN ENVIRONMENTS: A REVIEW - Krupnova, Tatyana; Rakova, Olga; Udachin, Valerii; Gavrilkina, Svetlana; Bondarenko, Kirill (GEOMATE Journal, 2023)
The study of natural and anthropogenic geochemical processes is important for identifying and preventing sources of environmental pollution. Isotopic ratios are used for lead (Pb) analysis in the environment, which is important because Pb is a toxic anthropogenic metal. Copper (Cu) and zinc (Zn), however, are ubiquitous metals, essential or toxic to organisms depending on their concentration, therefore research into their concentrations is useful for health risk assessments. This review presents the state of the art in Cu, Pb and Zn isotope studies applied in natural and urban environments. Although the study of Cu and Zn isotopes remains less developed than more that of lead isotopes, we can assess their relevance as a tracer of metals in the environment. We present the principles of isotope measurements from collecting samples to mass spectrometry analysis. To understand the fate of Cu, Pb, and Zn released into the environment by anthropogenic activities, we summarize the main processes governing the distribution of these metals in different environmental matrices. The matrices include atmospheric aerosols, dust, lake and river sediments, soils and other natural and artificial materials. The focus of the review is on the isotope fractionation affects which can modify the initial signature of the various sources. We suggest that the signatures of isotopes are defined for the main natural and anthropogenic sources of Cu, Pb, and Zn in the environment. This literature review points out current knowledge gaps and proposes future directions to make Cu, Pb, and Zn isotopes a relevant tracer of the sources and fates in the natural and urban environments.